2002
DOI: 10.1590/s0100-41582002000200014
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento de cultivares de meloeiro e melancia inoculados com Acremonium cucurbitacearum e Monosporascus cannonballus

Abstract: O colapso em cucurbitáceas é uma síndrome complexa na qual podem estar envolvidos numerosos agentes fitopatógenos, sendo bastante freqüente o ataque associado de vários deles. No presente trabalho é apresentado o comportamento de 19 cultivares de meloeiro (Cucumis melo) e duas de melancia (Citrullus lanatus), cultivadas no Brasil, frente a Acremonium cucurbitacearum e Monosporascus cannonballus, dois dos patógenos fúngicos associados a esta síndrome em diversos países. Todas as cultivares de meloiro e melancia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…These results agree with previous research that already indicated melon and watermelon as the most susceptible crops to this pathogen, although the cultivars used here are different from those evaluated previously. In fact, pathogenicity studies conducted up to the present time with commercial hybrids of melon and watermelon have not yet found any resistance to M. cannonballus (Armengol et al, 1998;Davis et al, 2008;Martyn & Miller, 1996;Mertely et al, 1993;Sales Júnior et al, 2002;Wolff & Miller, 1998 Regarding reisolation frequency of M. cannonballus, also melon and watermelon showed the highest values. In a similar work, 2016;Beltrán et al, 2008;Cohen, Burger, Horev, Porat, & Edelstein, 2005;Demartelaere, Freitas, Soares, Queiroz, & Sales Júnior, 2015;Edelstein, Cohen, Burger, & Shriber, 1999;Kim et al, 2016;Louws et al, 2010;Park et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…These results agree with previous research that already indicated melon and watermelon as the most susceptible crops to this pathogen, although the cultivars used here are different from those evaluated previously. In fact, pathogenicity studies conducted up to the present time with commercial hybrids of melon and watermelon have not yet found any resistance to M. cannonballus (Armengol et al, 1998;Davis et al, 2008;Martyn & Miller, 1996;Mertely et al, 1993;Sales Júnior et al, 2002;Wolff & Miller, 1998 Regarding reisolation frequency of M. cannonballus, also melon and watermelon showed the highest values. In a similar work, 2016;Beltrán et al, 2008;Cohen, Burger, Horev, Porat, & Edelstein, 2005;Demartelaere, Freitas, Soares, Queiroz, & Sales Júnior, 2015;Edelstein, Cohen, Burger, & Shriber, 1999;Kim et al, 2016;Louws et al, 2010;Park et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…These results agree with previous research that already indicated melon and watermelon as the most susceptible crops to this pathogen, although the cultivars used here are different from those evaluated previously. In fact, pathogenicity studies conducted up to the present time with commercial hybrids of melon and watermelon have not yet found any resistance to M. cannonballus (Armengol et al., ; Davis et al., ; Martyn & Miller, ; Mertely et al., ; Sales Júnior et al., ; Wolff & Miller, ). King, Davis, Zhang, and Crosby () reported some melon cultivars belonging to the types Conomom, Inodorus, Cantalupensis and Agrestis as resistant to M. cannonballus , but the fruits produced by them have no commercial value, presenting low or no quality for the market.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The expansion of culture, allied with intensive and continuous cultivation without the adoption of integrated management practices, has contributed to increasing the incidence and severity of various diseases. Among them, the Monosporascus root rot and vine decline (MRRVD), caused by the fungus Monosporascus cannonballus Pollack & Uecker, which is present in the main melon-producing areas in the states of RN and CE (ANDRADE et al, 2005;SALES JÚNIOR et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Countless control strategies against this disease have been tested, either in isolation or in association with others, but, none of them showed efficiency. However, they can be effective when sustainable measures are incorporated (MEDEIROS et al, 2008), such as the use of green fertilisation (SALES JÚNIOR et al, 2017), post-harvest residue destruction (RADEWALD; FERRIN; STANGHELLINI, 2004), chemical control (PIVONIA et al, 2010), application of essential oils (FERNANDES et al, 2015;AWAD, 2016), use of plant-growth-promoting bacteria (ANTONELLI et al, 2013), use of biocontrol agents (ALEANDRI et al, 2015) and grafting on hybrid rootstocks of Cucurbita (AL-MAWAALI et al, 2016;EDELSTEIN et al, 2017).…”
Section: Introductionmentioning
confidence: 99%